2022
DOI: 10.3389/fnagi.2022.935781
|View full text |Cite
|
Sign up to set email alerts
|

tDCS over the primary motor cortex contralateral to the trained hand enhances cross-limb transfer in older adults

Abstract: Transferring a unimanual motor skill to the untrained hand, a phenomenon known as cross-limb transfer, was shown to deteriorate as a function of age. While transcranial direct current stimulation (tDCS) ipsilateral to the trained hand facilitated cross-limb transfer in older adults, little is known about the contribution of the contralateral hemisphere to cross-limb transfer. In the present study, we investigated whether tDCS facilitates cross-limb transfer in older adults when applied over the motor cortex (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 83 publications
1
3
0
Order By: Relevance
“…Interestingly, consistent with the ‘neural overlap hypothesis’, in the c-tDCS but not in the s-tDCS group we observed a medium-sized positive correlation between DBT performance variability and Wii scores. Such near motor transfer effects have recently been observed by [85], manifested as improved cross-limb transfer from the trained to the untrained hand after anodal tDCS over rM1 in older adults. Similarly, we hypothesize that participants in our study were able to successfully use the movement solutions learned during DBT training onto an untrained balance task which also requires a comparable movement pattern in terms of body’s centre of mass (COM) control and displacement.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Interestingly, consistent with the ‘neural overlap hypothesis’, in the c-tDCS but not in the s-tDCS group we observed a medium-sized positive correlation between DBT performance variability and Wii scores. Such near motor transfer effects have recently been observed by [85], manifested as improved cross-limb transfer from the trained to the untrained hand after anodal tDCS over rM1 in older adults. Similarly, we hypothesize that participants in our study were able to successfully use the movement solutions learned during DBT training onto an untrained balance task which also requires a comparable movement pattern in terms of body’s centre of mass (COM) control and displacement.…”
Section: Discussionsupporting
confidence: 56%
“…Interestingly, consistent with the 'neural overlap hypothesis', in the c-tDCS but not in the s-tDCS group we observed a medium-sized positive correlation between DBT performance variability and Wii scores. Such near motor transfer effects have recently been observed by [85], manifested as improved cross-limb transfer from the trained to the untrained hand after anodal tDCS over rM1 in older adults.…”
Section: Pfc and Balance Training-induced Transfermentioning
confidence: 55%
“…28 Moreover, anodal AtDCS of apparently unrelated spared CSNs on the unaffected side improved hindlimb skilled motor function; this finding is consistent with the phenomenon of "ipsilesional control" observed in prior studies of central nervous system injuries. 8,46,48 Retrograde and anterograde labeling revealed that AtDCS promoted neural connections on the affected side; this may explain the observed improvement of skilled motor function following stimulation. The role of the mTOR pathway, a critical regulator of neuronal axon regeneration, in repairing central nervous system injuries has been extensively studied.…”
Section: Discussionmentioning
confidence: 93%
“…45 Another study indicated that AtDCS of the unaffected primary motor cortex (responsible for controlling the dominant hand) can improve motor function in older adults, suggesting that ipsilesional control may serve as a potential mechanism for promoting motor function recovery in patients. 46 Researchers elicited latent potential in the unaffected hemisphere and established a novel sensory feedback pathway for the paralyzed hand by manipulating the peripheral nerve through cervical nerve relocation in a preclinical study on animals. 8 In our previous study, AtDCS also exhibited potential in alleviating neuropathic pain after spinal cord injury in preclinical models.…”
Section: Discussionmentioning
confidence: 99%